Bias and Error Detection in Property Tax Administration - Cheng, Pao Lun (Management Science, 1976)
Reform of property tax administration to insure uniform assessment has received increasing attention. Tax administrators at local levels have responded accordingly. A practical scheme for monitoring appraisal biases and errors that cause departure from assessment uniformity has however, been lacking. This paper proposes a stochastic model of biases and errors in assessment administration and transforms it into a regression scheme for estimating bias and errors arising from growth, market and appraising processes. The model is then approximately validated for use in detecting biases and errors by any municipality interested in maintaining assessment uniformity.